2017
DOI: 10.1007/s10439-016-1788-y
|View full text |Cite
|
Sign up to set email alerts
|

Pubovisceralis Muscle Fiber Architecture Determination: Comparison Between Biomechanical Modeling and Diffusion Tensor Imaging

Abstract: Biomechanical analysis of pelvic floor dysfunction requires knowledge of certain biomechanical parameters, such as muscle fiber direction, in order to adequately model function. Magnetic resonance (MR) diffusion tensor imaging (DTI) provides an estimate of overall muscle fiber directionality based on the mathematical description of water diffusivity. This work aimed at evaluating the concurrence between pubovisceralis muscle fiber representations obtained from DTI, and the maximum principal stress lines obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…On the whole muscle level, DTI has been used in combination with tractography algorithms to measure changes in muscle architecture with passive length changes (9,10,62,83). DTI has also proven useful in biomechanical modeling studies, where information about fiber orientation is essential to accurately simulate the anisotropic behavior of muscle tissue (1,12,86). DTI has also been used to study changes in muscle fiber structure (DTI indexes) and (64); B], using information from anatomical scans and diffusion tensor imaging (DTI) tractography.…”
Section: Diffusion Imagingmentioning
confidence: 99%
“…On the whole muscle level, DTI has been used in combination with tractography algorithms to measure changes in muscle architecture with passive length changes (9,10,62,83). DTI has also proven useful in biomechanical modeling studies, where information about fiber orientation is essential to accurately simulate the anisotropic behavior of muscle tissue (1,12,86). DTI has also been used to study changes in muscle fiber structure (DTI indexes) and (64); B], using information from anatomical scans and diffusion tensor imaging (DTI) tractography.…”
Section: Diffusion Imagingmentioning
confidence: 99%
“…The levator ani muscle bore high Y–Z shear stress to prevent the pelvic viscera from excessive downward movement. According to previous studies, the levator ani muscle has fiber orientation ( 18 ). It holds a strong load-bearing capacity along the horizontal fiber direction, while its vertical fiber direction cannot bear excessive load.…”
Section: Discussionmentioning
confidence: 99%
“…The puborectalis muscle is more important than the pubococcygeus muscle and the iliococcygeal muscle. Previously, the anorectal angle and levator plate were considered to be good parameters to evaluate the pelvic oor structure [18] ,which plays an important role in defecation. However, this study suggested that the puborectalis muscle plays a decisive role in the evaluation of the pelvic oor structure.…”
Section: Discussionmentioning
confidence: 99%